PELAKSANAAN PENGAWASAN OLEH KEMENTERIAN PERHUBUNGAN TERHADAP KOORDINATOR SATUAN PELAYANAN TERMINAL BANDAR RAYA PAYUNG SEKAKI DALAM PENERAPAN PROTOKOL KESEHATAN COVID-19 DI KOTA PEKANBARU TAHUN 2019-2021 - Tia Rahmayanti; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Bandar Raya Payung Sekaki Terminal is a transportation service center between cities and between provinces, which has been planned by the local government for orientation and transfer between transportation modes. This terminal is an implementation of the Pekanbaru City Government's desire to have a land transportation facility that can support good and planned operations. The purpose of this study was to determine the implementation of supervision by the Ministry of Transportation of the Coordinator of the Bandar Raya Payung Sekaki Terminal Service Unit in the Implementation of the Covid-19 Health Protocol in Pekanbaru City in 20192021 and to determine the Inhibiting Factors in Supervision. This research use desciptive qualitative approach. In collecting data, researchers used the techniques of Observation, Interview, and Documentation. The results of the research on the implementation of supervision have not been carried out optimally. This can be seen from the supervision of related parties that has been carried out but many drivers and passengers still violate the Covid-19 health protocol rules. The inhibiting factors that affect the implementation of supervision are the existence of rules for the implementation of the Covid-19 health protocol, such as not all entrances to the hand sanitizing facility or providing hand washing facilities properly, the lack of functioning of infrastructure around the terminal, and lack of public awareness. Keywords: Supervision, Covid-19 Health Protocol